A fluorescent calixarene-based dimeric capsule constructed via a MII–terpyridine interaction: cage structure, inclusion properties and drug release. Issue 40 (20th June 2018) - Wang, Jun-Fang; Huang, Li-Yuan; Bu, Jian-Hua; Li, Shao-Yong; Qin, Su; Xu, Yao-Wei; Liu, Jun-Min; Su, Cheng-Yong
Abstract : A fluorescent calixarene-based dimeric capsule has been constructed via a M II –terpyridine interaction, and can capture mercaptopurine in solution and crystalline state and control drug release in PBS accompanied with fluorescence recovery. Abstract : Two analogues of capsule-like fluorescent cages have been constructed by dimerization of terpyridine-containing calixarene derivatives utilizing a M II –terpyridine (M = Zn and Cd) interaction. 1 H NMR spectral studies show that the self-assembled molecular capsulesZn4 L12 andCd4 L12 have a highly symmetrical D 4h -structure. The encapsulation of the anticancer drug mercaptopurine in their cavities has been documented by NMR, ESI-TOF-MS, fluorescence switching, and molecular simulation, indicating that strong S–π and π–π interactions between drug and cage are of importance for the host–guest binding. The nanoscale cages exhibit excellent behaviors to control the release of mercaptopurine in phosphate buffered saline solution (pH = 7.4). These results further highlight the potential of self-assembledZn4 L12 cages for drug-carrier applications.